Mepolizumab for severe eosinophilic asthma: a real-world snapshot on clinical markers and timing of response. (2nd December 2019) - Caminati, Marco; Cegolon, Luca; Vianello, Andrea; Chieco Bianchi, Fulvia; Festi, Giuliana; Marchi, Maria R; Micheletto, Claudio; Mazza, Francesco; Tognella, Silvia; Senna, Gianenrico
ABSTRACT: Background : Few studies have provided real-world evidence of mepolizumab efficacy and safety. We aimed to evaluate mepolizumab for severe eosinophilic asthma in daily clinical practice. Research design and methods : Patients included in the RINOVA (Interdisciplinary Network for the management of severe asthma in Veneto region, Italy) database were investigated. Blood eosinophil count, forced expiratory volume in 1 second, % of predicted (FEV1%), fractional exhaled nitric oxide (FeNO), asthma control test (ACT), oral steroid (OCS) intake, and exacerbation rate were evaluated during mepolizumab treatment. Results : 69 patients were enrolled (mean age: 55.1 years; 60.9% females). A significant improvement was detected at one month with respect to blood eosinophils (median level at baseline: 710/μl; −620/μl, p < 0, 001), FEV1% (median value at baseline 87; range: 79–101; +4, p = 0.001) and ACT (median value at baseline 18; range: 14–20.5;+4, <0.001). A significant reduction of FeNO was observed six months after the treatment start, when the exacerbation rate and the mean OCS dose significantly decreased (respectively: Δ reduction −3; p < 0.001 and −5 mg; p < 0.001). Conclusions : Our study provides real-world evidence of mepolizumab safety and confirms its dramatic steroid sparing effect. The greatest clinical change (ACT and FEV1) was observed within the first month.